Impact of Technology Readiness on User Satisfaction: Evidence Customer Intention to Use Mobile Banking in Punjab - Maham Aslam; Maham Aslam; Hafiz Muhammad Sajjad (Journal of Business & Tourism, 2021)
Technology advancement in the payment systems have led to more noteworthy access to formal financial framework.The desire of this study is to contemplate the factors that impact the intention to utilize mobile banking in Pakistan with view of using technology readiness acceptance model (TRAM). This study tests how the antecedents of technology readiness affect the intention to use mobile banking. The hypothetical model of this study is the blend of technology readiness (TR) and technology acceptance model (TAM), while the mediating role of user satisfaction fully mediates, that when the user perceives easy to use the technology due to effect of technology readiness to the adopting mobile banking. This study collected data from five commercial bank of Punjab such as Askari Bank, Allied bank, United bank, Bank Alfalah, Muslim commercial bank, Standard chartered bank and there are 450 responded as the utilization of mobile banking is sufficient, advance and time saving technology. However, it is accomplishing with the help of model. The discussion on the results of hypothesis testing and the conclusion both are presenting as associated section of the study.